A score-based performance assessment of maternal and child health services provided by USHA of Rajkot city - Ankit M Sheth; Anupam Banerjee; Amiruddin M Kadri; Matib Rangoonwala; Dipeshkumar D Zalavadiya; Niravkumar B Joshi (Wolters Kluwer Medknow Publications, 2017)
Background: Urban Social Health Activists (USHAs) are the grass root health care workers of urban areas. There are 290 USHAs distributed in various Urban Health Centers (UHCs) of Rajkot city. Objectives: To compare the (i) effectiveness of the training received by the USHAs on their knowledge and counseling skills (ii) knowledge and counseling skills of USHAs on the awareness and utilization of Maternal and Child Health (MCH) care services by their beneficiaries. Methods: This cross-sectional study involved 32 USHAs and 416 beneficiaries served by the same USHAs. 32 USHAs serving in the same field practice area for more than two years were randomly selected. The beneficiaries were those mothers who had a child between 1-2 years age, and who had availed their antenatal and postnatal services in the same area. A scoring system was used to assess the knowledge and counseling skills of the USHAs and the knowledge and utilization of services by their beneficiaries. Results: The utilization of health services was significantly more in the beneficiaries who were serviced by USHAs having comparatively better knowledge (72.7% vs. 35.3%) and counseling skills (62.2% vs. 30.6%). The median score for knowledge (41 vs. 30) and counseling skills (20 vs. 16) of the USHAs was found to be more (P < 0.05) in those who had undertaken induction training. Conclusions: Induction training helped the USHAs to improve their knowledge and counseling skills. Utilization of MCH services was more in those areas served by USHAs having better knowledge and counseling skills.